2013
DOI: 10.29074/ascls.26.4.200
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Safety and Healthcare Quality in the 21st Century—Competencies Required of Future Medical Laboratory Science Practitioners

Abstract: LEARNING OBJECTIVES1. Describe the IOM competencies practitioners need in order to deliver quality healthcare. 2. Identify methods to integrate evidence-based medicine for improving healthcare safety into the MLS curricula. 3. Describe exercises to employ in MLS curricula to develop problem-solving skills required for participation in quality improvement projects. 4. Identify key aspects of delivering patient-centered care to include in MLS curricula. ABSTRACTHealthcare quality has yet to meet the aims of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Additionally, the high level of service quality decides patient satisfaction and patient satisfaction importantly leads hospitals to obtain sustainable competitive advantage in the unstable market (Gustavsson, et al, 2016, Materla, et al, 2017. Finally, several studies have explored that quality of service can lead to patient satisfaction (Morris, 2013;Siverbo, 2014, Wongrukmit, & Thawesaengskulthai, 2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the high level of service quality decides patient satisfaction and patient satisfaction importantly leads hospitals to obtain sustainable competitive advantage in the unstable market (Gustavsson, et al, 2016, Materla, et al, 2017. Finally, several studies have explored that quality of service can lead to patient satisfaction (Morris, 2013;Siverbo, 2014, Wongrukmit, & Thawesaengskulthai, 2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study systematically constructed physicians' competency model. Research result had revealed that the desirable Thai Medical competencies were consisted with several factors as 1 As for Model for Thai Physician Competency Development, it was found that consisting with (1) Individual Development (2) Organizational Development (3) Network Development (4) Enabling Environment Development. This result was coincident with the work of American Hospital Association on the study on Lifelong Learning Physician competency development that stated that hospitals play a vital role in education and training and provide the milieu in which physicians and other clinicians practice.…”
Section: Discussionmentioning
confidence: 99%
“…No professional curricula adequately prepare future healthcare practitioners-including medical laboratory science professionals-with all competencies necessary to deliver quality healthcare. Practicing evidence-based medicine, focusing on quality improvement, using information technology, delivering patient-centered care and working as part of interdisciplinary teams are identified by the IOM as the five core competencies that every healthcare practitioner needs to effectively provide healthcare [2]. As for Thailand as same as situation of an oversea facing in term of healthcare mentioned above, apart from that, there is also evidence showing that Thai medical personnel are now facing a critical issue caused by litigation.…”
Section: Introductionmentioning
confidence: 99%
“…Nel 2004-2006 un'approfondita indagine su "Diritti dei cittadini e laboratorio analisi" [15] esamina il rispetto dei quattordici diritti fondamentali (misure preventive, accesso, informazione, consenso, libera scelta, tempo del paziente, privacy e confidenzialità, standard di qualità, sicurezza, innovazione, evitare sofferenze, trattamento personalizzato, reclamo, risarcimento) con risultati soddisfacenti, seppure a macchia di leopardo, sul territorio nazionale e con molti miglioramenti possibili nell'informazione, nel consenso e nella documentazione-tracciabilità dei dati. Oggi questi punti rappresentano la base dei Laboratori ad alto valore aggiunto, che determina anche cambiamenti competenziali [16].…”
Section: Medicina DI Laboratorio Centrata Sul Pazienteunclassified